Tipdatingbeast: an r package to assist the implementation of phylogenetic tip‐dating tests using beast. (25th October 2016) - Rieux, Adrien; Khatchikian, Camilo E.
Abstract: Molecular tip dating of phylogenetic trees is a growing discipline that uses DNA sequences sampled at different points in time to coestimate the timing of evolutionary events with rates of molecular evolution. In this context, beast, a program for Bayesian analysis of molecular sequences, is the most widely used phylogenetic tool. Here, we introducetipdatingbeast, anr package built to assist the implementation of various phylogenetic tip‐dating tests usingbeast .tipdatingbeast currently contains two main functions. The first one allows preparing date‐randomization analyses, which assess the temporal signal of a data set. The second function allows performing leave‐one‐out analyses, which test for the consistency between independent calibration sequences and allow pinpointing those leading to potential bias. We apply those functions to an empirical data set and supply practical guidance for results interpretation.